Comunicación en redes y discursos de odio en el contexto español - Moreno López, Roberto; Morales Calvo, Sonia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
In the framework of the CONTACT project, 20 interviews were conducted with young people in Spain between 18 and 30 years old, with the main objective of increasing awareness and understanding of hate speech among Spanish youth. The main results show that hate speech is part of communication on the Internet and social networks, and that the reach and impact of hate speech is reflected on the streets and online. Young people understand that hate speech is directed at social groups determined by their body, culture, ethnicity, and sexual orientation, although they recognize it in the private sphere.